Stunted lives, stagnant economies : poverty, disease, and underdevelopment - Stillwaggon, Eileen, 1949- (Rutgers University Press, 1998)
"Stunted Lives, Stagnant Economies describes in vivid detail the living conditions of the poor in developing countries and the diseases and injuries that result from this environment of need. Most of the diseases that affect the poor - cholera, summer diarrhea, tuberculosis, lice, worms, leprosy - result from the poverty of their environment. Poverty also determines the availability and effectiveness of the medical response. Using Argentina as a case study, Eileen Stillwaggon argues that making good health available to everyone is not a scientific problem but an economic one." "The debt crisis of the 1980s and the subsequent structural adjustment policies adopted by most developing countries exacerbated the problems faced by the poor. What kind of future can a nation build when the health of the majority of the population - its workforce - is at risk or compromised because social services have been reduced? Without adequate health care and social services, people cannot live up to their potential, and the spiral of poverty continues. But there are ways to fight this cycle of poverty. With a clear vision of the future, Stillwaggon offers practical, low-cost solutions to promote human development and economic growth."--Jacket